CORAK BUDAYA JAWA DALAM ISLAM - Jamal Ghofir; Sofiatul Avivah (Program Studi Manajemen Dakwah, Fakultas Dakwah, Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Abstract Javanese society is very thick with various traditions and cultures. Although in Java the majority of the population is Muslim, it cannot be denied that even in religion there is a Javanese cultural style that cannot be abandoned. The history of the process of meeting between religion and local culture is full of dynamics. However, because Islam spread in Java in a peaceful way, so Islam was well received and led to the acculturation of Islam and Javanese culture. Keywords: Tradition, Culture, Java, Islam.